Nursing Diagnosis Risk for falls: prevalence and clinical profile of hospitalized patients - Melissa de Freitas Luzia; Marco Antonio de Goes Victor; Amália de Fátima Lucena (Universidade de São Paulo, 2014)
OBJECTIVES: to identify the prevalence of the Nursing Diagnosis (ND) Risk for falls in the hospitalizations of adult patients in clinical and surgical units, to characterize the clinical profile and to identify the risk factors of the patients with this ND.METHOD: a cross-sectional study with 174 patients. The data was collected from the computerized nursing care prescriptions system and on-line hospital records, and analyzed statistically.RESULTS: the prevalence of the ND Risk for falls was 4%. The patients' profile indicated older adults, males (57%), those hospitalized in the clinical units (63.2%), with a median length of hospitalization of 20 (10-24) days, with neurological illnesses (26%), cardio-vascular illnesses (74.1%) and various co-morbidities (3±1.8). The prevalent risk factors were neurological alterations (43.1%), impaired mobility (35.6%) and extremes of age (10.3%).CONCLUSION: the findings contributed to evidencing the profile of the patients with a risk of falling hospitalized in clinical and surgical wards, which favors the planning of interventions for preventing this adverse event.